Damage Assessment Method for Light Steel Roof Frames: Case Study of Government Buildings - Maskur, Atep; Wibowo, M. Agung; Winarno, Setya (Universitas Muhammadiyah Yogyakarta, 2024)
The tornado disaster in Ciamis Regency damaged 55 buildings, including the Panawangan District Office. The aim of this research was to identify the condition and level of damage to the Light Steel Roof Frame Structures that were damaged and determine the ranking or percentage of damage. By making direct observations at the location of the incident. The result is that: The roof covering element uses zincalum metal with the batten frame partially damaged on the left side of the building above the hall and the right corner of the front of the building. The battom chord, top chord and web elements are partially detached. The trim element made of GRC material is damaged. came loose, and the Gypsum ceiling elements with hollow frames fell on the outside and inside the hall. The percentage of damage obtained is 14.50% and the damage level ≤ 30% is categorized as Light Damage.